STRATEGIC CONVERGENCE AND COMPETITION IN THE INDO-PACIFIC REGION: POLICY OPTIONS FOR PAKISTAN (Margalla Papers, 2020)
With Indo-Pacific being the stage for US-China strategic influence, South East Asia’s geopolitical scenario is likely to be transformed considerably. By declaring India as a Net Security Provider, the US has backed its outreach in the region by officially adjoining Pacific and Indian Oceans as the Indo-Pacific region. Major countries of the region including China, Russia, India, and Pakistan are in the phase of diversifying and reconfiguring their relationships. Within this scenario, Pakistan and India are likely to pursue their strategic interests that take them in opposite directions. While the US endows India with its strategic partner status, CPEC in Pakistan has emerged as a litmus test for China’s BRI. The contestation is to have a direct bearing on the strategic matrix of South Asia generally and Pakistan particularly. This qualitative research under the framework of realist/neo-realist and complex interdependence’s assumptions undertakes to account for this Sino-US strategic convergence and competition that is leading to a security dilemma in South Asia with implications for Pakistan. It concludes cooperation between the US and China is to enhance Pakistan’s security both internal and external while competition is to erode it. Alongside, this paper formulates some policy options for Pakistan’s decisionmakers for ensuring the security and socio-economic development of the country. Bibliography EntryYounus, Khadija. 2020. "Strategic Convergence and Competition in the Indo-Pacific Region: Policy Options for Pakistan." Margalla Papers 24 (1): 81-96.